Implementation of Micro Teaching in Developing Basic Teaching Skill Of Tadris IPS’s Students at IAIN Jember - Elisa Pravianti (heritage, 2022)
The purpose of this research is to describe the cognitive stage of micro teaching in developing basic teaching skills of students of IAIN Jember social studies study program, to describe the stage of implementing micro teaching in developing basic teaching skills of students of IAIN Jember social studies study program  and  to describe reverse stage of micro teaching in developing basic teaching  skills  of students social studies study program of IAIN Jember. The research uses a qualitative approach and descriptive type of research. The location of this research is in the social studies study program of IAIN Jember. Determination  of  informants using purposive teachnique. Data collection teachnique by interview, observation and documentation. Data analysis used interactive models of Miles, Huberman, and Saldana. The validity of the data used technical triangulation and sourch triangulation. The results of this study indicate the cognitive stage of micro teaching of IPS Tadris Study Program IAIN Jember was carried out at the beginning of the offline meeting, with the basic teaching skills material and the concept of micro teaching. The implemtation stage of the micro teaching of IPS Tadris study programs at IAIN Jember was carried out offline and online by carrying out 2 activities, namely limited training namely isolated and integrated as well as practical examination activities and the reserve stage of micro teacing of IPS IAIN Jember Study program carried out by students with oral observers and written observers while supervising lecturers assessed the lesson plans, micro teaching performance and  material mastery. The conclusion of this research is that the cognitive stage in micro teaching is crried out at the beginning of the meeting with the provision of material on the concept of micro teaching, the implementation stage of micro teaching is carried out in two activities, namely limited practice and practical exams and the reverse stage of micro teaching is carried out by students and supervisors.